The Effectiveness of Animation Video to Improve The Student’s Learning Interest in Thematic Lesson In The Third Grade of Girimulyo Elementary School In 2020/2021 - Siti Anifah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to increase students' interest in learning in sub-theme 4, the subject of changes in the form of objects around me in class 3 at Girimulyo Elementary School in 2020/2021. This type of research is the Classroom Piercing Research (PTK) which is carried out in 2 cycles. The stages of each cycle are planning, implementing, observing and reflecting. The author makes observations and provides an evaluation test in each cycle to determine the development of students. In cycle 1, students who scored above the KKM reached 70%. After the improvement was carried out in cycle 2, the scores of students who reached the KKM were 93%. This result shows that video animation can increase students' interest in learning in Thematic learning for grade 3 SDN Girimulyo.